Development of a PIV-vectored RSV vaccine: Preclinical evaluation of safety, toxicity, and enhanced disease and initial clinical testing in healthy adults - Tang, Roderick S.; Spaete, Richard R.; Thompson, Mark W.; MacPhail, Mia; Guzzetta, Jeanne M.; Ryan, Patricia C.; Reisinger, Keith; Chandler, Patricia; Hilty, Milo; Walker, Robert E.; Gomez, Margarita M.; Losonsky, Genevieve A. (Vaccine, 2008)
MEDI-534 is a bivalent live attenuated vaccine candidate against human respiratory syncytial virus (hRSV) and human parainfluenza virus type 3 (hPIV3) that was previously shown to be immunogenic and to protect rodents and African green monkeys from wild-type (wt) hRSV challenge. We performed further preclinical evaluations to address the safety of MEDI-534 prior to human testing. MEDI-534 did not predispose rodents to enhanced RSV disease following wt-RSV challenge, and the tissue tropism of the chimeric virus was confined to the respiratory tract. Representative clinical trial material did not produce toxicity in rats. In adults, MEDI-534 was highly restricted in replication, did not boost RSV and PIV3 antibody titers, and produced no medically significant vaccine-related adverse events thereby warranting further evaluation in pediatric populations.